EFFECT OF METHACRYLATE ON SALIVARY GLAND FUNCTION - Senchakovych, J.V.; Yeroshenko, G.A.; Kazakova, K.S.; Bilash, S.M. (World of Medicine and Biology, 2014)
The increase in average life expectancy, the pathology of dental hard tissues, and especially of periodontal tissue, leading to progressive loss of teeth, and therefore increases the need for dentures. Acrylic plastic that is now used as a base material, can not be indifferent to oral tissues, in particular for the mucosa. Effect of metharylate on function of the salivary glands is multifactorial. According to the literature data, it leads first to a acute decrease of secretion. Resulting in disturbances of homeostasis of the oral cavity, reducing the protective function of the oral mucosa and lower quality of masticatory function.
Keywords: methacrylate; dentures; salivary glands